Social media as advertising medium for hotel guest at luxury hotels in City of Manila - Antolin, Del Carlo B. Ba as, Paulo Angelo Catli, Kristian Ericsson I. Espino, Areeya Jane C. Ibano, Nichelle N. Mariano, Janica L. Villaruel, Prinz Willis S. 4 0 16; 5 (2014)
A study focusing on social media as an advertising medium for guests of luxury hotels within the City of Manila was originally conducted to answer and to provide supporting ideas if this social media advertisement has a significant role for a guest's solidity purchasing intentions. A study trying to figure if the hotel's products, promotions, services and public relations are associated with a hotel having an effective social media advertisement. In order to gather the needed data, the researchers conducted a survey with the questionnaires sent through the guests' social media accounts. Every answer is then tallied by the researcher's Google account. With the study having to take note of products, promotions, services, and public relations as its variables, ANOVA one way was used to compute for the output of the survey. Through ANOVA, the researchers came up with the final computed output being greater than the final tabular output which meant that the study's null hypotheses were rejected. After completing all the final output, and discussing the results of the survey and computations, only then were the recommendations formulated.
Undergraduate Thesis: (B.S. Hotel and Hospitality Management) - Pamantasan ng Lungsod ng Maynila 2014.
Keywords: 2 -- 0; 6; 20; 20; 2